Development and validation of a regional-scale high-resolution unstructured model for wave energy resource characterization along the US East Coast. (June 2019) - Allahdadi, M. Nabi; Gunawan, Budi; Lai, Jonathan; He, Ruoying; Neary, Vincent S.
Abstract: Leveraging the high-performance computing capability at one of the US Department of Energy's (USDOE) National Laboratories, an ultra-high-resolution Simulating WAves Nearshore (SWAN) model suitable for wave energy project feasibility studies is developed for the US East Coast Region. This model uses an unstructured mesh with a coastal resolution of 200 m. It is forced by Climate Forecast System Reanalysis wind fields with spatial and temporal resolutions of 0.312° and 1 h at the surface, and by wave parameters from the global WAVEWATCH III model along the model's open boundaries. It is the first USDOE regional wave hindcast model for the US East Coast developed according to International Electrotechnical Commission standards for wave energy resource assessment and characterization. The present study focuses on the development and validation of this ultra-high resolution large-scale model, including source model selection, sensitivity studies, and model performance evaluation for a wave energy resource characterization application. Highlights: An unprecedented ultra-high-resolution model simulated waves along the US East Coast. Model parameters were finalized using extensive sensitivity and calibration runs. Model was verified using wave data from 18 NDBC coastal and offshore buoys. Six IEC parameters were successfully simulated and validated.